Biochar from Different Sections of Oil Palm Trunk Improves Biomass Accumulation and Nutrient Uptake in Pre-Nursery Oil Palm (Elaeis guineensis Jacq.) in Ultisol Media - Ebsan Marihot Sianipar; Siti Mardiana; Syahbudin Hasibuan (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
The production of high quality seedlings is dependent on soil as planting media. Application of biochar derived from oil palm trunk onto oil palm seedling  has been scarcely studied, especially on ultisol planting media. This research investigated the effect of oil palm trunk biochar on vegetative growth and nutrient uptake of belowground and aboveground tissues of oil palm (Elaeis guineensis Jacq) in ultisol pre-nursery planting media. Three types of oil palm trunk biochar derived from top, middle, and bottom section were used in this research. The application rates were 1, 2, 3 and, 4 % (w/w) during 12 weeks in  a green house. This experiment used a non factorial randomized complete block design with three replications. The addition of biochars derived oil palm trunk (OPT) amendment significantly increased stem diameter, plant height, root biomass, shoot biomass. The highest respon rasio (RRs) for root and shoot biomass was 0.40, and 0.55, respectively, recorded at 2% application rates. The highest increase of N, P, and K uptake for belowground and aboveground tissues were resulted from B3 (3 % biochar top section), B2 (2 % biochar top section), and B2 (2 % biochar top section) treatments, respectively. Overall, the addition of biochar derived top section OPT at 2 % (w/w) could enhance stem diameter, RRs plant biomass, N, P, K uptake of belowground and aboveground tissues. The addition of biochar OPT at 2 % (w/w) should be recommendation in order to used as rate of biochar OPT for ultisols ammendment in oil palm pre-nursery